2012
DOI: 10.1007/s10570-012-9695-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drying method on the properties and nanoscale structure of cellulose whiskers

Abstract: Cellulose whiskers were prepared from wood-and cotton-based microcrystalline cellulose and dried by two methods: freeze-drying or air-drying. The effect of drying method on the properties and structure of the whiskers were studied. Furthermore, the influence of the source of cellulose on the nanoscale structure was investigated. Drying method was observed to slightly influence the thermal stability of cellulose whiskers, whereas the char residue varied significantly depending on the drying process performed. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 24 publications
1
13
0
3
Order By: Relevance
“…As previously reported272829, cellulose nanocrystals could be distinguished on the film surface with no particular orientation; however, the long axis of the nanocrystals appeared to be parallel to the film surface. AFM observation of the hemicellulose films revealed long filaments on the surface of the GM films.…”
Section: Resultssupporting
confidence: 77%
“…As previously reported272829, cellulose nanocrystals could be distinguished on the film surface with no particular orientation; however, the long axis of the nanocrystals appeared to be parallel to the film surface. AFM observation of the hemicellulose films revealed long filaments on the surface of the GM films.…”
Section: Resultssupporting
confidence: 77%
“…It is known that the packing of cellulose microfibrils could be affected by rehydration in water (Rämänen et al 2012) (Zimmerley et al 2010). The comparison Cellulose of SFG spectra of AWD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These drying processes are well described in the literature (Maloney et al 1998;Ping et al 2001;Park et al 2007;Eyholzer et al 2010;Quiévy et al 2010;Peng et al 2012;Rämänen et al 2012;Voronova et al 2012). Peng et al (2012) reported about the high potential of spray drying for production of powdered particles of cellulose nanocrystal (CNC) and NFC.…”
Section: Morphologymentioning
confidence: 91%
“…There is a large body of literature concerning freeze drying of cellulose particles in near nanodimensions (Helbert et al 1997;Jin et al 2004;Viet et al 2007;AgodaTandjawa et al 2010;Lu and Hsieh 2010;Quiévy et al 2010;Rämänen et al 2012;Voronova et al 2012). On the contrary, there are a limited number of reports on spray drying in the context of NFC (Quiévy et al 2010;Vartiainen et al 2011;Kolakovic et al 2012;Peng et al 2012), and only a few studies are dealing with the redispersibility of dried MFC or NFC (Beck et al 2012;Missoum et al 2012).…”
Section: Introductionmentioning
confidence: 99%